Pengaruh Model Estafet Writing Berbantuan Cerita Bergambar Terhadap Keterampilan Menulis Teks sederhana Siswa kelas III Sekolah Dasar - Hapsari, Fitra Hesti; SB, Nugraheti Sismulyasih (Paedagogie, 2026)
This research was motivated by the low simple text writing skills among third-grade elementary school students caused by difficulties in expressing ideas in written form and weak spelling application. Less varied learning models and media also affected student learning outcomes, with 53% of students not yet achieving the Learning Objective Achievement Criteria (KKTP). This research aims to analyze the effect of the estafet writing model assisted by picture story media on simple text writing skills and to describe the improvement in student activities. The research method used a quantitative approach with a quasi-experimental design in the form of Nonequivalent Control Group Design. The sample used in this study consisted of 15 third-grade students from SDN Tlogopandogan 1 as the experimental class and 14 third-grade students from SDN Tlogopandogan 2 as the control class. The research instruments consisted of writing skills tests and student activity observation sheets. Data analysis using SPSS 27 included normality tests, homogeneity tests, hypothesis tests, N-gain tests, and student activity analysis. The research results showed a value of 2,087 greater than of 2,052 with a significance of 0,046 < 0,05, which means there is a significant effect. The experimental class experienced an average increase from 66,4 to 78,13 with an N-gain of 0,34 in the moderate category, while the control class increased from 64 to 70 with an N-gain of 0,16 in the low category. Student activity in the experimental class reached 70,62%, higher than the control class at 56,25%. It can be concluded that the estafet writing model assisted by picture story